2017
DOI: 10.1093/brain/aww334
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between flortaucipir PET tau binding and amyloid burden, clinical diagnosis, age and cognition

Abstract: The relation between tau, amyloid and cognition has yet to be fully defined. Using flortaucipir (18F-AV-1451) PET tau imaging in patients with varying amyloid and cognitive status, Pontecorvo et al. suggest that development of tau beyond the mesial temporal lobe is associated with, and may be dependent on, amyloid accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
283
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(333 citation statements)
references
References 57 publications
47
283
2
1
Order By: Relevance
“…We and others have previously shown that [F-18]-AV-1451 binds with strong affinity to paired helical filament (PHF)-tau aggregates in AD brains and those that form as a function of age [11,13,12,24,31]. In agreement with these observations, patients clinically diagnosed with dementia of AD type and mild cognitive impairment (MCI) exhibit significantly higher in vivo [F-18]-AV-1451 retention than cognitively normal individuals in regions that are known to contain an elevated burden of tau lesions in AD [10,7,8,3,30,25,6,19]. …”
Section: Introductionmentioning
confidence: 65%
“…We and others have previously shown that [F-18]-AV-1451 binds with strong affinity to paired helical filament (PHF)-tau aggregates in AD brains and those that form as a function of age [11,13,12,24,31]. In agreement with these observations, patients clinically diagnosed with dementia of AD type and mild cognitive impairment (MCI) exhibit significantly higher in vivo [F-18]-AV-1451 retention than cognitively normal individuals in regions that are known to contain an elevated burden of tau lesions in AD [10,7,8,3,30,25,6,19]. …”
Section: Introductionmentioning
confidence: 65%
“…In addition to our two main analyses with local and inferior temporal tau, we have included a supplemental figure and table exploring the relationship between atrophy and entorhinal tau. Elevated AV-1451 in the medial temporal lobes has previously been related to increasing age by other research groups (Brier et al, 2016; Gordon et al, 2016; Jack et al, 2016; Pontecorvo et al, 2017; Schöll et al, 2016), and there is some research indicating that entorhinal tau may be more closely associated with higher levels of amyloid than inferior temporal tau burden (Vemuri et al, 2017). Fig.…”
Section: Methodsmentioning
confidence: 90%
“…The current patient groupings thus represent one approach to phenotypic heterogeneity in AD and are not meant to imply that PCA patients who subsequently develop memory deficits follow the same disease course as purely amnestic AD patients. Fourth, the present study did not compare the ability of PET tau and amyloid imaging results to account for clinical symptoms, nor did it consider possible interactions between tau and amyloid pathology (Ittner & Götz, ; see also Pontecorvo et al, ). Fifth, tau PET imaging data from cognitively normal controls were not available.…”
Section: Discussionmentioning
confidence: 96%